Perbandingan IBAC dan ABAC Sebagai Strategi Keamanan Siber Berbasis Zero Trust Architecture (ZTA) - Erwin Maulana; Herdi Ashaury; Melina (Institut Teknologi Garut, 2026)
The rapid development of web technologies has increased exposure to various types of cyberattacks, making traditional perimeter-based security approaches less effective. Zero Trust Architecture (ZTA), with its principle of “never trust, always verify,” offers a more adaptive approach to addressing modern threats. This study aims to analyze and compare the effectiveness of two access control models within the ZTA framework—Identity-Based Access Control (IBAC) and Attribute-Based Access Control (ABAC)—in enhancing web application security. The research employs a quantitative experimental approach by developing two ZTA-based web application prototypes implementing IBAC and ABAC. Three common cyberattacks—SQL Injection, Cross-Site Scripting (XSS), and Brute Force—are tested using Detection Rate as the evaluation parameter. The results show that both models achieve a 100% Detection Rate against all simulated attacks, indicating that they provide an equivalent level of protection within the context of this experiment. Nevertheless, conceptual analysis reveals that ABAC offers advantages in terms of granularity and contextual awareness, as it is capable of dynamically evaluating user attributes, object attributes, and environmental conditions. These characteristics make ABAC more aligned with the principle of continuous verification in Zero Trust, particularly for long-term implementation in modern web applications.